Developing Google Sites-assisted collaborative learning materials to learn quadratic function - Mukhlishoh, Fatimah Nur; Fahmi, Syariful (Universitas Ahmad Dahlan, 2024)
This study was motivated by the need for teaching materials obtained from the results of questionnaire analysis, namely 69 out of 70 students stated that they needed interactive and fun website-based teaching materials. Students also experience difficulties in learning mathematics with the methods applied by teachers and material that is considered difficult, namely the quadratic function with a percentage of 70%. This study aims to develop website-based interactive teaching materials with a collaborative approach assisted by Google Sites that are valid and practical. The research used the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were students of class X-5 and X-3 SMA Negeri 1 Kasihan, while the research object was Funmath Quadratic Function website. Data were collected through interviews, observations, material and media expert validation questionnaires, and student response questionnaires in small and large class trials. The results showed that the Funmath Quadratic Function website teaching materials developed were very valid with a percentage of 86% according to material experts and 86.5% according to media experts. In addition, this teaching material is also very practical with a score of 88.6% in the small class trial and 95.18% in the large class trial. The results showed that this teaching material is very valid and practical, so it can help the process of learning mathematics on quadratic function material that is more interactive and fun. In this study, it is recommended to add a variety of content and interactive activities for better understanding of the quadratic function. In addition, training for teachers and students needs to be provided so that the use of the website is maximized. Periodic evaluation is also important to maintain the quality and relevance of teaching materials.